Relative abundances and concentrations of individual n-alkanes, total Concentration of odd n-alkanes, average chain length and the carbon preference index obtained from the Eemian sediment sequence retrieved from Sokli (Finland) in 2010 - Anna Plikk; Stefan Engels; Maria Fernández-Fernández; Christos Katrantsiotis; Malin E Kylander; Ludvig Löwemark; Sakari Salonen; Minna Väliranta; Karin Helmens (PANGAEA, 2025)
This dataset provides the relative abundances (Rel_abn) and concentrations (Conc; presented as ug/g dry weight) of individual n-alkanes, as well as the Total Concentration of odd n-alkanes (ug/g dry weight), average chain length (ACL) and the carbon preference index (CPI). The dataset consists of 59 samples obtained from the Eemian sediment sequence retrieved from Sokli (Finland) in 2010. All parameters are presented against both depth (m) and age (ka BP). The dataset provides information on Eemian vegetation and ecosystem dynamics (Katrantsiotis et al., 2021). Lipid extracts were obtained for a total of 59 samples and separated into different fractions following the laboratory protocol presented in Katrantsiotis et al. (2021). The hydrocarbon fractions were then analyzed by Gas Chromatography-Mass Spectrometry (Shimadzu-QP2010 Ultra system) for n-alkane identification and quantification. CPI was calculated as: CPI = SUModd/SUMeven; (ACL) was determined as: ACL = SUM(n * Cn)/SUM(Cn), where Cn is the concentration (mg/g dry weight) of odd chain n-alkanes. The analyses were carried out at the Stable Isotope Laboratory, Stockholm University, Sweden. A previous version of this dataset can be found on the Bolin Climate Centre database (https://bolin.su.se/data/katrantsiotis-2021-sokli-1)